Stimulasi Perkembangan Kecerdasan Spiritual Anak Melalui Program Santri Cilik Di TK Islam Alam Nusantara - Airin Mutiarasari; Andri Isnaeni (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2024)
Early childhood is a critical period for stimulating the development of various potentials, including spiritual intelligence. Spiritual intelligence in children is one of the essential aspects that should be nurtured from an early age. Considering the concurrent growth and development of children alongside the rapid advancement of the times and its potential negative influences, developing spiritual intelligence is crucial as a foundation for children's character. This study aims to investigate the development of children's spiritual intelligence through the Santri Cilik program at TK Islam Alam Nusantara. The research method employed is qualitative, utilizing data collection techniques such as interviews, observations, and documentation. The data analysis procedures include data reduction, data display, and conclusion drawing. The findings of the study indicate that children's spiritual intelligence can be effectively developed through the Santri Cilik program at TK Islam Alam Nusantara using various methods, including storytelling, worship practices, Al-Mahfudzot, Islamic songs and clapping, involving children in social activities, play and interaction with the environment, role-playing, and modeling by teachers and parents.